Measurement of strain in InGaN/GaN nanowires and nanopyramids. (1st April 2015) - Stankevič, Tomaš; Mickevičius, Simas; Schou Nielsen, Mikkel; Kryliouk, Olga; Ciechonski, Rafal; Vescovi, Giuliano; Bi, Zhaoxia; Mikkelsen, Anders; Samuelson, Lars; Gundlach, Carsten; Feidenhans'l, Robert
<x xml:space="preserve">Abstract</x> The growth and optoelectronic properties of core–shell nanostructures are influenced by the strain induced by the lattice mismatch between core and shell. In contrast with planar films, nanostructures contain multiple facets that act as independent substrates for shell growth, which enables different relaxation mechanisms. In this study, X‐ray diffraction data are presented that show that InαGa1−αN shells grown on GaN cores are strained along each of the facets independently. Reciprocal space maps reveal multiple Bragg peaks, corresponding to different parts of the shell being strained along the individual facet planes. The strained lattice constants were found from the positions of the Bragg peaks. Vegard's law and Hooke's law for an anisotropic medium were applied in order to find the composition and strain in the InGaN shells. A range of nanowire samples with different InGaN shell thicknesses were measured and it is concluded that, with an In concentration of around 30%, major strain relaxation takes place when the thickness reaches 23 nm. InGaN shells of 6 and 9 nm thickness remain nearly fully strained biaxially along each of the <inline-graphic xlink:href="ark:/27927/pgjdnd8b0b" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> facets of the nanowires and the <inline-graphic xlink:href="ark:/27927/pgjdnd8b1v" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> facets of the nanopyramids.